Dynamic recrystallization behavior of a typical nickel-based superalloy during hot deformation - Chen, Xiao-Min; Lin, Y.C.; Wen, Dong-Xu; Zhang, Jin-Long; He, Min (Materials in engineering, 2014)
•The dynamic recrystallization behavior of a typical nickel-based superalloy is investigated.•The segmented models are proposed to describe the kinetics of DRX for the studied superalloy.•The dynamically recrystallized grain size can be well characterized by a function of Z parameter. The dynamic recrystallization (DRX) behavior of a typical nickel-based superalloy is investigated by the hot compression tests. Based on the conventional DRX kinetics model, the volume fractions of DRX are firstly estimated. Results show that there is an obvious deviation between the experimental and predicted volume fractions of DRX when the forming temperature is below 980°C, which is induced by the slow dynamic recrystallization rate under low forming temperatures. Therefore, the segmented models are proposed to describe the kinetics of DRX for the studied superalloy. Comparisons between the experimental and predicted results indicate that the proposed segmented models can give an accurate and precise estimation of the volume fractions of DRX for the studied superalloy. In addition, the optical observation of the deformed microstructure confirms that the dynamically recrystallized grain size can be well characterized by a power function of Zener–Hollumon parameter.